ETIKA POLITIK ARISTOTELES: Kohesivitas Etika dan Politik - Hadi, Rahmad Tri; Arrasyid, Arrasyid (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This article specifically describes and analyzes the cohesiveness between ethics and politics from Aristotle's thought. More specifically, he has written his thoughts in a book entitled Politics which has presented the concept of building the basic structure of the state and how to manage and distribute social justice (goodness). In human life, ethics and politics seem inseparable from human civilization. This is because this is one of the fundamentalist parts of the human paradigm and is difficult to separate. If politics is understood, as a “match”;